Monster's ball - Daniels, Lee, 1959-; Addica, Milo.; Rokos, Will.; Forster, Marc, 1969-; Thornton, Billy Bob.; Ledger, Heath, 1979-2008.; Berry, Halle; Diddy, 1969-; Mos Def (Rapper); Calhoun, Coronji; Boyle, Peter, 1935-2006.; Schaefer, Roberto; et al. ([United States] : Studio S : Trimark Home Video : Distributed by Lions Gate Home Entertainment, 2002)
Hank and Leticia inhabit stark, queasy realities of the contemporary South, he as a death row corrections officer and she as the soon-to-be widow of an inmate whose execution Hank helps conduct. In the aftermath of the execution, both lose their children to tragic deaths and they form an unlikely bond.
Special features: 16x9 widescreen with aspect ratio 2.35:1 -- Over one hour of behind-the-scenes footage -- Two complete audio commentaries: Audio commentary by Mark Forster and Roberto Schaefer ; Autio commentary by Halle Berry and Billy Bob Thornton -- Never-before-seen deleted scenes and outtakes -- IFC's Anatomy of a scene -- Language: English 5.1 Dolby digital -- Subtitles: English.
Originally produced as a motion picture in 2001.
Special features: behind-the-scenes footage; audio commentary by director Marc Forster and director of photography Roberto Schaefer; audio commentary by Halle Berry and Billy Bob Thornton; never-before-seen deleted scenes and outtakes; theatrical trailer; IFC's anatomy of a scene.
Director of photography, Roberto Schaefer ; editor, Matt Chess ;̌ music composer, Asche and Spencer ; costume designer, Frank Fleming ; production designer, Monroe Kelly.
Billy Bob Thornton, Heath Ledger, Halle Berry, Sean Combs, Mos Def, Will Rokos, Milo Addica, Coronji Calhoun, Peter Boyle.
DVD, 5.1 Dolby digital, (16x9 ; 2.35:1).
English dialogue, English and Spanish subtitles.
Keywords: Man-woman relationships -- Drama; Racism -- Drama; Video recordings for the hearing impaired; Fiction films; Feature films; Feature films